Perancangan Sistem Informasi Rekam Medis Pada UPT Puskesmas Cinta Manis Banyuasin Berbasis Website - Anggi Rizki Ramayanti Anggi (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2021)
Medical records are system for managing patient data, documents namely patient identity, examination results, treatment, actions and services that have been provided to patients. Cinta Manis Health Center's medical record system still managed manually so that errors often occur and become less effective and efficient. With problems that arise such as taking long time to check patient data, research aims to design Medical Record Information System the UPT Puskesmas Cinta Manis. By using website, it is hoped the data processing process will more structured and provide data information quickly and precisely. The method used is waterfall and system design with usecases, activity diagrams and class diagrams. Computerized medical records make easier for officers manage patient medical record data and reports.